2019
DOI: 10.1016/j.pnpbp.2019.109662
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 PUFA metabolism and brain modifications during aging

Abstract: In Canada, 5.5 million (16% of Canadians) adults are >65 years old and projections suggest this number will be approximately 20% of Canadians by 2024. A major concern regarding old age is a decline in health, especially if this entails a loss of self-sufficiency and independence caused by a decline in cognition. The brain contains 60% of fat and is one of the most concentrated organs in long chain omega-3 fatty acids such as docosahexaenoic acid (DHA). During aging, there are physiological modifications in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 144 publications
(172 reference statements)
1
27
0
Order By: Relevance
“…Generally, fish require proper www.nature.com/scientificreports/ amounts of dietary PUFAs as they play an important role in the correct development of neural system 41 . Furthermore, altered dietary SFA and n6 intake have been related to behavioural and cognitive impairments in humans and rodents 26 . The FTIR analysis of brain samples evidenced that increasing inclusion levels of dietary BSF meal caused a drastic decrease of unsaturated fatty acids and carbohydrates in brain, mainly in Hi75 and Hi100 groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, fish require proper www.nature.com/scientificreports/ amounts of dietary PUFAs as they play an important role in the correct development of neural system 41 . Furthermore, altered dietary SFA and n6 intake have been related to behavioural and cognitive impairments in humans and rodents 26 . The FTIR analysis of brain samples evidenced that increasing inclusion levels of dietary BSF meal caused a drastic decrease of unsaturated fatty acids and carbohydrates in brain, mainly in Hi75 and Hi100 groups.…”
Section: Discussionmentioning
confidence: 99%
“…While a diet rich in n3 fatty acids has generally been associated with a lower risk to develop neurodegenerative and cardiovascular diseases in humans and animal models 23,24 , the chronic ingestion of n6 and SFAs has been related to wide loss of brain volume and synapses 25 and to behavioural impairments such as dementia 26 . Impaired behaviour and learning have also been related to a reduction in gut microbiota variability 27 , a condition often related to a n6 and SFAs rich diet 28 .…”
mentioning
confidence: 99%
“…The brain consists of straight-chain monocarboxylic acids ranging from C 12 to C 26 , and omega-3 (n-3) and omega-6 (n-6) fatty acids are most abundant (Kishimoto et al, 1969;Siegel, 1999). Docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) are prominent polyunsaturated fatty acids (PUFA) in the brain that are derived from alpha-linolenic acid (ALA), an omega-3 fatty acid (Chappus-McCendie et al, 2019). Arachidonic acid (AA) and docosatetraenoic acid (DPA) constitute a large proportion of PUFA's that are derived from linolenic acid (LNA), an omega 6 fatty acid (Leonard et al, 2000;Sinclair et al, 2007).…”
Section: Brain Lipids In Healthy Aging and Ad Pathologymentioning
confidence: 99%
“…Brain Lipids Changes in Aging These PUFA's are incorporated into membrane phospholipids and therefore play a significant role in structural integrity and function of cell membranes. Lipid metabolism is changed during aging (Montanini et al, 1983;Yehuda et al, 2002;Whelan, 2008;Denis et al, 2015;Cutuli, 2017;Chappus-McCendie et al, 2019), as shown by a decline in omega-3 fatty acids and an increase in lipid peroxidation (Chen et al, 2017). Omega-3 fatty acids have antioxidant properties, and a lack of these fatty acids in one's diet may accelerate neuronal degeneration (Yehuda et al, 2002;Janssen and Kiliaan, 2014).…”
Section: Factors That Affect Brain Lipids Demographic Factors That Inmentioning
confidence: 99%
“…The main classes of PUFAs belong to the omega-3 one, which comprises α-linolenic acid (ALA, 18:3 ω-3), eicosapentaenoic acid (EPA, 20:5 ω-3) and docosahexaenoic acid (DHA, 22:6 ω-3) and to the omega-6 one, which comprises linoleic acid (LA, 18:2 ω-6) and arachidonic acid (ARA, 20:4 ω-6) [14] (Table 1). DHA and ARA are the most important PUFAs in the brain [15]. In particular, DHA constitutes over 90% of the ω-3 PUFAs and 10–20% of total lipids in the brain [16].…”
Section: Introductionmentioning
confidence: 99%